1998
DOI: 10.1203/00006450-199806000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Factors in the Determination of Final Height in Subjects Born Small for Gestational Age

Abstract: The aim of this study was to identify factors predictive of individual final height (FH) in subjects born small for gestational age (SGA). All full-term singleton subjects born SGA (birth weight and/or length <3rd percentile) during the period 1971-1978, matched with appropriate birth weight for gestational age (AGA) subjects (birth weight between 25th and 75th percentile) were followed from birth to FH and evaluated before puberty at a mean age +/- SD of 6.1 +/- 0.7 y and after puberty at a mean age of 20.8 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
96
2
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 17 publications
15
96
2
2
Order By: Relevance
“…Furthermore, it has been shown that children who were born SGA and displayed catch-up growth during infancy showed an increased body fat mass with a more central fat distribution in comparison with children who were born with normal birth size (6). This increased growth velocity of adiposity persists until adulthood, as evidenced by relative increase in BMI (expressed in SDS) from childhood to adulthood, leading to a significantly increased percentage of body fat mass at the age of 25 y in individuals who were born SGA in comparison with control subjects (7,8). Catch-up growth has been suspected to favor later development of long-term metabolic complications associated with reduced fetal growth (9 -12).…”
mentioning
confidence: 99%
“…Furthermore, it has been shown that children who were born SGA and displayed catch-up growth during infancy showed an increased body fat mass with a more central fat distribution in comparison with children who were born with normal birth size (6). This increased growth velocity of adiposity persists until adulthood, as evidenced by relative increase in BMI (expressed in SDS) from childhood to adulthood, leading to a significantly increased percentage of body fat mass at the age of 25 y in individuals who were born SGA in comparison with control subjects (7,8). Catch-up growth has been suspected to favor later development of long-term metabolic complications associated with reduced fetal growth (9 -12).…”
mentioning
confidence: 99%
“…Infants born short for gestational age have an increased risk of short adult stature (17)(18)(19). Data from Barker's group indicate that being small at birth is a threat to cardiovascular health, especially if obese in adulthood.…”
mentioning
confidence: 99%
“…Although most affected infants show some degree of catchup in growth during the first years of life (AlbertssonWikland et al, 1993;Karlberg & Albertsson-Wikland, 1995), epidemiological studies have consistently shown a positive association between size at birth (i.e. birth weight or birth length) and height in children (Albertsson-Wikland et al, 1993;Bavdekar et al, 1999;Hadders-Algra & Touwen, 1990), adolescents (Bacallao et al, 1996;Ibanez et al, 2000;Paz et al, 1993;Rantakallio & von Wendt L., 1985;Westwood et al, 1983) and adults ( Karlberg & AlbertssonWikland, 1995;Karlberg & Luo, 2000;Leger et al, 1997;Leger et al, 1998;Nielen et al, 1984;Sorensen et al, 1999). A recent study of approximately 40,000 young men showed that there was a mean difference of more than 7 cm in height between men with a low and a high birth weight (< 2500 and > 4500 g, respectively), and a mean difference of almost 10 cm in height between men who were short and those who were long at birth (< 48 and > 55 cm, respectively;Tuvemo et al, 1999).…”
mentioning
confidence: 99%